Notes and fragments - Kant, Immanuel, 1724-1804 (Kant, Immanuel, 1724-1804. Works. 1992., 2005)
This volume provides the first ever extensive translation of the notes and fragments that survived Kant's death in 1804. These include marginalia, lecture notes, and sketches and drafts for his published works. They are important as an indispensable resource for understanding Kant's intellectual development and published works, casting new light on Kant's conception of his own philosophical methods and his relations to his predecessors, as well as on central doctrines of his work such as the theory of space, time and categories, the refutations of skepticism and metaphysical dogmatism, the the.